Effects of biodex balance training on symptomatic knee osteoarthritis in Rawalpindi: a randomized control trial - Samina Javed; Huma Riaz; Aruba Saeed; Ruqia Begum (Journal of the Pakistan Medical Association, 2020)
Abstract Objective: To determine the effect of Biodex training on lower limb functional performance, balance, pain and properioception in symptomatic knee osteoarthritis patients. Methods: It was a Randomized control study conducted in Armed forces Institute of Rehabilitation Medicine (AFIRM) from February to June 2018. Ethical approval from Riphah research ethical committee was taken. Study included 48 patients of both genders with age between 35-65 years and grade II, III bilateral knee osteoarthritis (Kellgren-Osteoarthritis classification). Patients with Past Knee surgery, knee injury, Recent Intra articular injection and with Rheumatoid Arthritis were excluded. Purposive sampling technique was used for sample selection. Patients were randomly allocated through sealed envelope method into Control group (n=24) and Experimental group (n=24). Control group received traditional exercise program while Experimental group received balance training on biodex & traditional exercise program. Assessment was taken at baseline and post intervention. Pain was assessed through Numeric pain rating scale (NPRS), Functional performance was assessed through Western Ontario and McMaster Universities Osteoarthritis index (WOMAC) and Time up and Go test (TUG), Balance was assessed through Biodex stability system this assessment include overall stability index, AP stability, ML stability, overall sway, AP sway and ML sway. Data was analyzed on SPSS version 21. Results: Participants of experimental group shows statically significant improvement in NPRS (P<0.005), Overall stability index (p=0.49) and in Anteroposterior stability index (p=0.046). Improvement in Mediolateral stability index (p=0.047) and overall sway index was (p=.049). Stability index improved in all direction except in Anteroposterior index in experimental group. Continuous...